Prevalence of newly diagnosed high blood pressure among female adults aged 18 to 50 years in south western Nigeria - Ngozi A. Ukangwa; Ijeoma Esiaba; Abolanle A.A. Kayode (Journal of Krishna Institute of Medical Sciences University)
Background: High blood pressure is well known as a significant determinant for the development of cardiovascular disease and a major cause of death globally. It usually shows no symptoms thus the term 'Silent Killer'. Scientific investigations reveal that women diagnosed with elevated blood pressure levels are particularly vulnerable to experiencing a faster decline in kidney function compared to their male counterparts. Aim and Objectives: This research study aimed to evaluate the prevalence of high blood pressure in females who are oblivious to their blood pressure condition. Material and Methods: A semi-structured questionnaire was completed by 280 females who came for a free medical outreach in the Ikenne Local Government Area. Blood pressure was obtained in compliance with standard procedure Data were evaluated and shown as numbers and percentages for categorical variables while continuous variables were represented as average mean and standard deviation. The relationships among data variables were assessed using linear regression and ANOVA with the level of significance at p < 0.05. Results: The mean age of the participants was 38.75 ± 9.18 years. Around 24% of people in this research had elevated blood pressure levels. The average values for both systolic and diastolic blood pressure were 125.74 ± 21.53 mmHg and 76.59 ± 13.77 mmHg, respectively, with a significance level of p < 0.05. A significant correlation was identified between systolic blood pressure and both age (r = 0.260, p < 0.05) and body mass index (r = 0.197, p = 0.02). Conclusion: Elevated blood pressure levels are still prevalent among females in south-western Nigeria. It can be linked to contributing factors like body mass index and age. Therefore, public health agencies, as well as health care practitioners, can deliberate on health policies prioritizing the reduction of this deadly disease condition among females by providing proper monitoring and effective management as well as encouraging routine blood pressure checks.